Penggunaan Bahasa Verbal Hipnoterapis dan Pengaruh Nonverbal Terhadap Pecandu Rokok: Suatu Kajian Neurospikolinguistik - Fetri Reni (Fakultas Sastra Universitas Ekasakti, 2017)
This research is aimed at finding the suggestion forms of verbal hypnoterapist language and its nonverbal reaction to cigarette suffering (clients). In collecting data is used observation method and non-Participant observation technique followed by recording and note taking method. The data is collected at one of hypnoteraphy clinic in Padang. In analyzing the data, the writer uses referential and pragmatic identity method. To finding data clearly, valuable, and easy to read is used descriptive statistic in order to know client condition and how far verbal hypnotherapist can influent to the client. Data is served in the formal and informal method. Based on the analysis is concluded that, somnabulistic is an important section in giving hypnotherapy suggestion. Using word “belatung” to AM client, “tikus” to WW client, and “ular” to IR client have a different reaction to each client. Client AM in the 21-27 scale, is a good suggestion. He is a Physical Sugestible who has right hemisfer domain. Client WW is an Emotional Sugestible, in the 21-27 also but she has dificulty in the open eyes trance, she is a middle suggestion who has left hemisfer domain and client IR has Intelectual Sugestible, who has critical analysis, in the 28-35. Beside that suggestions must have given reapeatly short, clear and motivation understandable langguage. Suggestions are in the plural and active sentences which avoid in using words “dont”, “will”, “no”. Overall, cigarette suffering is a person who suffer from unconsious mind or psychomatis that can give negative effect to his healhty. Giving suggestion motivation sentences in hypnotherapy can hamper the critical factor of client and finally, can solve client suffer problems.